Nacre-inspired magnetically oriented micro-cellulose fibres/nano-hydroxyapatite/chitosan layered scaffold enhances pro-osteogenesis and angiogenesis. (December 2022) - Ge, Yu-Wei; Chu, Min; Zhu, Zi-Yang; Ke, Qin-Fei; Guo, Ya-Ping; Zhang, Chang-Qing; Jia, Wei-Tao
Abstract: In situ regeneration of large-segment bone defects is a difficult clinical problem. Here, we innovatively developed magnetically oriented micro-cellulose fibres using nano-hydroxyapatite/chitosan (CEF/Fe3 O4 /HA/CS) and loaded an NFκB pathway inhibitor on the surface of magnetically oriented cellulose fibres (CEF/Fe3 O4 /HA/CS/PQQ) prepared as a layered bioscaffold. CEF/Fe3 O4 /HA/CS/PQQ was constructed by layering HA/CS sheets. Nano-hydroxyapatite was deposited on the surface of cellulose fibres, then the magnetic nanoparticles on the cellulose fibres were aligned on the surface of chitosan under a magnetic field. Oriented cellulose fibres enhanced the compressive properties of the scaffold, with an average maximum compressive strength of 1.63 ​MPa. The CEF/Fe3 O4 /HA/CS/PQQ layered scaffold was filled into the body, and the acute inflammatory response (IL-1β and TNF-α) was suppressed through the early sustained release of PQQ. The CEF/Fe3 O4 /HA/CS/PQQ-layered scaffold further inhibited the osteoclasts differentiation. It was further found that the nano-hydroxyapatite on the surface of oriented cellulose fibres promoted the formation and migration of new blood vessels, accelerated the processing of collagen-I fibres to cartilage, and endochondral ossification. Hence, the development of the CEF/Fe3 O4 /HA/CS/PQQ layered scaffold with oriented fibres guides bone growth direction and pro-osteogenesis activity and provides a novel strategy for the in situ regeneration of large segmental bone defects. Graphical abstract: Image 1 Highlights: Oriented microcellulose fibers contain nano-hydroxyapatite is prepared by mimicking the extracellular matrix of bone tissue. Inspired by the hierarchical structures of mollusk nacre, the layered scaffolds was constructed. Oriented microcellulose fibers promote the high expression of collagen type 1. The layered scaffolds also promote the formation of new blood vessels.